Three new species of Lycianthes (Solanaceae) from Panama - Dean, Ellen; Poore, Jennifer; Kang, Hannah (Phytotaxa, 2020)
Three Panamanian cloud forest species in the genus Lycianthes are newly described: L. coloradensis, from the Ngäbe-Buglé Comarca; L. fortunensis from Chiriquí Province, Veraguas Province, and the Ngäbe-Buglé Comarca; and L. talamancensis from Bocas del Toro and Chiriquí provinces. All three species are woody vines with tan, yellow, or orange-brown multangulate-stellate trichomes and entire to nearly entire white to purple corollas. In terms of vegetative morphology and trichome characteristics, L. coloradensis most closely resembles L. purpusii of Mexico, Guatemala, and Honduras, L. fortunensis resembles the widespread L. multiflora, and L. talamancensis resembles L. hortulana of Honduras, El Salvador, and Nicaragua. This article provides species descriptions, maps of geographic distributions, specimen images of each species, and comparison tables of morphological characters used to separate L. coloradensis, L. fortunensis and L. talamancensis from similar species.